Aggrieved White Men and the Danger They Pose to Democracy and Peace - Bernd Reiter (Social Sciences)
This article examines the resurgence of fascism and white supremacy politics in Western societies through the lens of status, honor, and dignity. By focusing on the political appeal of leaders like Donald Trump, Jair Bolsonaro, Viktor Orbán, and others, this study argues that these leaders resonate with primarily white, male supporters who feel that their social status and cultural identity are under threat. Drawing on works by Isabel Wilkerson, Ashley Jardina, and Arlie Hochschild, this analysis highlights how anxieties surrounding demographic shifts, perceived “status loss”, and narratives of cultural displacement fuel support for authoritarian policies. It posits that contemporary right-wing movements in the US, Europe, and Latin America are less about economic grievances and more about defending a social hierarchy in which white identity is paramount. This pursuit, while objectively not the same, still mirrors struggles among historically marginalized communities, as discussed by scholars like Bhimrao Ambedkar and Gopal Guru, challenging traditional rational-choice models of political behavior. Relying on an auto-ethnographic account obtained from living in one of the US’s most conservative regions, the West Texas plains, this study suggests that authoritarianism’s appeal lies in its promise to restore a social order steeped in white male dominance, showing how feelings of honor and pride can override democratic principles and fuel political polarization. Ultimately, this article cautions that a social science approach relying solely on rational actor models risks overlooking the potent influence of status anxieties in shaping modern political landscapes, with significant implications for democracy and justice.